The future of evolutionary behavioral biology - Theo C. M. Bakker; James F. A. Traniello; Tim R. Birkhead; Monika Borgerhoff Mulder; Bernard Crespi; Niels J. Dingemanse; Raghavendra Gadagkar; Ashleigh S. Griffin; Mark E. Hauber; Bert Hölldobler; John L. Hoogland; Sarah B. Hrdy; et al. (Behavioral Ecology and Sociobiology, 2026)

Why are larvae of the social parasite wasp Polistes sulcifer not removed from the host nest? - R. Cervo; F. R. Dani; C. Cotoneschi; C. Scala; I. Lotti; J. E. Strassmann; D. C. Queller; S. Turillazzi (Behavioral Ecology and Sociobiology, 2008)

Social parasitism of Polistes dominulus by Polistes nimphus (Hymenoptera, Vespidae) - R. Cervo; C. Stemmer; W. Castle; D. Queller; J. E. Strassmann (Insectes Sociaux, 2004)

Conflict over male parentage in stingless bees - E. Tth; D. C. Queller; A. Dollin; J. E. Strassmann (Insectes Sociaux, 2004)

Low relatedness and frequent queen turnover in the stenogastrine wasp Eustenogaster fraterna favor the life insurance over the haplodiploid hypothesis for the origin of eusociality - M. Landi; D. C. Queller; S. Turillazzi; J. E. Strassmann (Insectes Sociaux, 2003)

Co‐occurrence in nature of different clones of the social amoeba, Dictyostelium discoideum - A. Fortunato; J. E. Strassmann; L. Santorelli; D. C. Queller (Molecular Ecology, 2003)
The social amoeba, Dictyostelium discoideum , produces a multicellular fruiting body and has become a model system for cell–cell interactions such as signalling, adhesion and development. However, unlike most multicellular organisms, it forms by aggregation of cells and, in the laboratory, forms genetic chimeras where there may be competition among clones. Here we show that chimera formation is also likely in nature, because different clones commonly co‐occur on a very small scale. This suggests that D. discoideum will likely have evolved strategies for competing in chimeras, and that the function of some developmental genes will be competitive. Natural chimerism also makes D. discoideum a good model organism for the investigation of issues relating to coexistence and conflict between cells.

Swarm‐founding in the polistine wasps: the importance of finding many microsatellite loci in studies of adaptation - M. T. Henshaw; J. E. Strassmann; D. C. Queller (Molecular Ecology, 2001)
We developed 52 microsatellite loci for the wasp, Polybioides tabidus , for the purpose of studying the evolution and inclusive fitness consequences of swarm‐founding. The large number of loci is important for three reasons that may apply to many other systems. Heterozygosity was low in our target species, yet we found enough polymorphic loci for accurate kinship studies in this species. Many monomorphic loci were polymorphic in other polistine wasps, making comparative studies possible. Finally, enough loci amplified over a broad range of species to add a historical dimension. We sequenced six loci in other polistine wasps and used the flanking sequences to construct a phylogeny. Based on this phylogeny, we infer that swarm‐founding has evolved independently three times in the polistine wasps.

The independent origin of a queen number bottleneck that promotes cooperation in the African swarm-founding wasp, Polybioides tabidus - M. T. Henshaw; J. E. Strassmann; D. C. Queller (Behavioral Ecology and Sociobiology, 2000)

Absence of within-colony kin discrimination: foundresses of the social wasp, Polistes carolina , do not prefer their own larvae - J. E. Strassmann; P. Seppä; D. C. Queller (The Science of Nature, 2000)

Computer software for performing likelihood tests of pedigree relationship using genetic markers - K. F. Goodnight; D. C. Queller (Molecular Ecology, 1999)
Molecular techniques are making ever more genetic markers available for use in parentage assignment, and measures of relatedness. We present a program, Kinship , designed to use likelihood techniques to test for any non‐inbred pedigree relationship between pairs of individuals, using single‐locus codominant genetic markers. Kinship calculates the likelihood that each pair of individuals in a data set are related by a given pedigree hypothesis, and likelihood ratios for any pair of hypotheses. The program also uses a simulation routine to attach statistical significance to its results.

Trinucleotide microsatellite loci for a social wasp, Polistes - J. E. Strassmann; K. Barefield; C. R. Solís; C. R. Hughes; D. C. Queller (Molecular Ecology, 1997)